Qualitative Traits Characterization of Three Local Chicken Ecotypes of Western Zone of Tigray, Northern Ethiopia - Markos , S.; Belay, B.; Dessie, T. (International Journal of Poultry Science, 2020)
Background and Objective: Characterization of local chicken ecotypes based on qualitative morphological traits is very crucial to generate useful information for designing appropriate holistic breeding strategies that enhance sustainable management, utilization and conservation of the local chicken genetic resources. The study was conducted to characterize three local chicken ecotypes (lowland, midland and highland) in the western zone of Tigray, Ethiopia based on qualitative morphological traits. Materials and Methods: A total of 1642 matured chickens (619 from lowland, 548 from midland and 475 highland chicken ecotypes) were observed for phenotype expression of qualitative traits (body shape, spur presence, head shape, comb size, comb type, comb color, eye color, skin color, plumage color, breast feather color, back feather color, neck feather color, shank color, feather morphology, feather growth, feather distribution, earlobe presence, earlobe color and shank feather). Descriptive statistics using frequency procedure of SPSS version 22 was used to analyze the observed qualitative traits. Kruskal-Wallis Test was employed to test the effects of chicken ecotypes and sexes on the distribution of the observed qualitative traits. Results: The frequency of the distribution of eye color, comb color, plumage color, breast feather color, back feather color, neck feather color, earlobe color and shank color were significantly varied across three chicken ecotypes and sexes. The distribution of head shape, feather morphology, feather growth, earlobe presence and shank feather were similar among chicken ecotypes and sexes. The distribution of skin color, feather distribution and comb type was significantly different among chicken ecotypes but not between chicken sexes. The distribution of body shape, spur presence and comb size was significantly varied between chicken sexes but not among chicken ecotypes. Conclusion: The Variations in qualitative traits of the three local chicken ecotypes indicated that there is genetic diversity of the chicken population of the three local chicken ecotypes that may call for designing community based genetic improvement programs.